EFEKTIVITAS MODEL DIRECT INSTRUCTION DALAM MENINGKATKAN KEMAMPUAN SISWA SMA NEGERI 1 BATAUGA MEMAHAMI NILAI DALAM FOLKLORE WANDIUDIU - Ria, Eva; Abbas, Asriani; Hasyim, Muhaammad (JURNAL ILMU BUDAYA, 2020)
This study aims (1) to explain the application of the direct instruction model in improving the ability of students at SMS Negeri 1 batauga to understand the value of Wandiudiu’s folklore and (2) explain the effectivennes of the direct instruction model in improving the ability of students of SMA Negeri 1 Batauga to understand the value of Wandiudiu’s folklore. The type of research used is the type of classroom action research or commonly known as PTK (classroom action research). This class action research applies several cycles in it’s implementation. The results showed that there was an increase in student learning process. Learning out comes in the control class show differences. However, this difference does not indicate a significant increase in learning outcomes. Cycle I reaches an average value of 70,61 and cycle II reaches an average value of 72,04. The results of both cycles are only in the sufficient category. Learning outcomes in the experimental class showed significant differences. Cycle I reached an average value of 78, 87 and was in the sufficient category, while cycle II achieved an average value of 85,17 and was in the goog category. The improvement of learning outcomes shows taht the effective direct instruction model is used to improve the ability of students of SMA Negeri 1 Batauga to understand the values in Wandiudiu’s folklore.